Risky sexual practices and related factors among ART attendees in Addis Ababa Public Hospitals, Ethiopia: A cross-sectional study - Bedru Abdo; Gerbaba Mulusew; Dessie Yadeta; Davey Gail (BMC, 2011)
Abstract Background Many HIV-positive persons avoid risky sexual practices after testing HIV sero-positive. However, a substantial number continue to engage in risky sexual practices that may further transmit the virus, put them at risk of contracting secondary sexually transmitted infections and lead to problems with drug resistance. Thus, this study was intended to assess risky sexual practices and related factors among HIV- positive ART attendees in public hospitals of Addis Ababa. Methods A cross-sectional study was conducted among ART attendees from February to March, 2009. Questionnaire-based face-to-face interviews were used to gather data. SPSS software was used to perform descriptive and logistic regression analyses. Results Six hundred and one ART attendees who fulfilled the inclusion criteria was included in the study and interviewed. More than one-third (36.9%) had a history of risky sexual practices in the three months prior to the study. The major reasons given for not using condoms were: partner's dislike of them, both partners being positive for HIV and the desire to have a child. Factors associated with risky sexual practices included: lack of discussion about condom use (Adjusted Odds Ratio (AOR = 7.23, 95% CI: 4.14, 12.63); lack of self-efficacy in using condoms (AOR = 3.29, 95% CI: 2.07, 5.23); lack of sexual pleasure when using a condom (AOR = 2.39, 95% CI: 1.52, 3.76); and multiple sexual partners (AOR = 2.67, 95% CI: 1.09, 6.57). Being with a negative sero-status partner (AOR = 0.33, 95% CI: 0.14, 0.80), or partners of unknown sero-status (AOR = 0.19, 95% CI: 0.09, 0.39) were associated with less risky practice. Conclusions A considerable proportion (36.9%) of respondents engaged in unprotected sexual intercourse, potentially resulting in re-infection by a new virus strain, other sexually transmitted infections and onward transmission of the HIV virus. Health education and counseling which focuses on the identified factors has to be provided. The health education and counseling can be provided to these people at ART appointments on follow- up care. It can be provided in a one-on-one basis or through patient group educational discussions at the clinics.